Osteogenesis Imperfecta: Multidisciplinary and Goal-Centered Care - Chang, Bryston; Keating, Sarah; Mikhael, Michel; Lim, Jina (American Journal of Perinatology Reports, 2022)
We describe a case of osteogenesis imperfecta (OI) in a late preterm female of 35-week gestation. The mother did have a history of substance abuse, poor prenatal care, and hypertension. On the day of delivery, an ultrasound revealed skeletal dysplasia and breech with nonreassuring fetal tracing, leading to an emergency cesarean. The clinical exam was concerning for OI, and postnatal care was focused on optimizing respiratory status and minimizing pain and discomfort during routine care. Genetics, endocrine, orthopaedics, and palliative care were all involved to diagnose and educate the family. Support and education were needed for bedside staff to minimize angst at performing routine care, given the high risk of fractures. While initially stable on minimal oxygen, once the diagnosis of type III OI was made, a progressively deforming condition with respiratory status decompensation, the family wished to minimize suffering, limited aggressive medical care, and focused on comfort. The infant eventually died from respiratory failure in the neonatal intensive care unit. We present this case to demonstrate the need for an interdisciplinary team approach to support both family and staff in cases of OI.
Keywords: osteogenesis imperfecta; prematurity; goals of care; multidisciplinary care